Family-based exome sequencing identifies rare coding variants in age-related macular degeneration. (3rd April 2020) - Ratnapriya, Rinki; Acar, İlhan E; Geerlings, Maartje J; Branham, Kari; Kwong, Alan; Saksens, Nicole T M; Pauper, Marc; Corominas, Jordi; Kwicklis, Madeline; Zipprer, David; Starostik, Margaret R; Othman, Mohammad; et al.
Abstract: Genome-wide association studies (GWAS) have identified 52 independent variants at 34 genetic loci that are associated with age-related macular degeneration (AMD), the most common cause of incurable vision loss in the elderly worldwide. However, causal genes at the majority of these loci remain unknown. In this study, we performed whole exome sequencing of 264 individuals from 63 multiplex families with AMD and analyzed the data for rare protein-altering variants in candidate target genes at AMD-associated loci. Rare coding variants were identified in the CFH, PUS7, RXFP2, PHF12 and TACC2 genes in three or more families. In addition, we detected rare coding variants in the C9, SPEF2 and BCAR1 genes, which were previously suggested as likely causative genes at respective AMD susceptibility loci. Identification of rare variants in the CFH and C9 genes in our study validated previous reports of rare variants in complement pathway genes in AMD. We then extended our exome-wide analysis and identified rare protein-altering variants in 13 genes outside the AMD-GWAS loci in three or more families. Two of these genes, SCN10A and KIR2DL4, are of interest because variants in these genes also showed association with AMD in case-control cohorts, albeit not at the level of genome-wide significance. Our study presents the first large-scale, exome-wide analysis of rare variants in AMD. Further independent replications and molecular investigation of candidate target genes, reported here, would assist in gaining novel insights into mechanisms underlying AMD pathogenesis.